Keterlibatan Pendidik Dalam Pengembangan Kurikulum Pendidikan Anak Usia Dini - Mushlih, Ahmad; Susilo, Errifa; Ninda Uminar, Ajeng (Institut Agama Islam Negeri Ponorogo, 2024)
Education continues to improve following the flow of the times. Changes in the world of education begin with changes in the curriculum. The cycle of curriculum change is dynamic and comprehensive at every level of education, including early childhood education (ECE). Researchers conduct research using qualitative methods with interview, observation and documentation techniques. The location of the study involved 34 early childhood education institutions of kindergarten units and Raudhatul Athfal in Tulungagung and surrounding areas. The results show that educators have an important role in transforming the quality of learning services through curriculum development. In addition, educators in developing the curriculum through several stages, namely planning, collaboration, implementation and evaluation of the curriculum. Therefore, educators as the spearhead of educational success have the task of improving the competence of excellent educators.